Midwifery tutors training program - syed, Shershah (Nepal Journal of Obstetrics and Gynaecology, 2018)
PAKISTAN has more than one forty eight (148) school of midwifery in different parts of country. Pakistan National Forum on Women's Health (PNFWH) realized that majority of these school of midwifery has no trained faculty to teach and train future midwives. It is also observed and shown in a study by UNICEF Pakistan that ninety percent midwives get their diploma in midwifery without doing a single delivery in labor room. To face this challenge PNFWH started a six month midwifery tutors training program at Koohi Goth Women Hospital (KGWH) in Karachi. Twenty five midwifery tutors from midwifery schools in different parts of country came to stay at KGWH for this program. They were taught to teach in class room with or without modern teaching aids. They were encouraged to use computer and should be able to do power presentation at the end of Theiler training. All tutors were posted in labor ward and train to do clinical teaching at the bed side and laboring women. The program was a great success. Up till now eleven batches were trained with the help of donors who are working in their midwifery schools. This paper discusses the issues related to tutors training and problems faced by midwifery schools in recruiting competent tutors.